Viability of liquid medium-inoculation of Rhizobium etli in planting furrows with common bean - Oliveira, Dâmiany Pádua; Soares, Bruno Lima; Martins, Fábio Aurélio Dias; Franceschini, Leandro Alex; Cardillo, Bruno Ewerton da Silveira; Rufini, Márcia; Morais, Augusto Ramalho de; Moreira, Fatima Maria de Souza; Andrade, Messias José Bastos de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the viability of liquid medium inoculation of Rhizobium etli in the planting furrow and to certify the efficiency of its strain UFLA 02-100 as a potential inoculant for common bean (Phaseolus vulgaris). The treatments consisted of three application rates of liquid inoculant applied in the planting furrows and one rate applied in common bean seed, besides two controls without inoculation. The inoculant contained 109 cells of Rhizobium etli mL-1. Regardless of the application method, the yield obtained with the inoculation was equivalent to that of N from urea; however, the application in the furrows, at 0.6 L ha‑1, is more advantageous due to the operational practicality and reduced costs.